United States : Financial Sector Assessment Program-Financial System Stability Assessment. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2015)
This paper discusses the results of the Financial System Stability Assessment on the United States made under the Financial Sector Assessment Program. It is found that welcome steps have been taken in strengthening the financial system. The Financial Stability Oversight Council now provides a useful forum for coordination, the regulatory perimeter has expanded, information sharing among agencies has improved, supervisory stress testing is leading changes in risk measurement and management, and new resolution powers have been established. However, new pockets of vulnerabilities have emerged, partly in response to the continuing search for yield. This requires a continuing focus on strengthening the micro and macroprudential framework.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet